Effects of vitamin D supplementation on metabolic parameters, serum irisin and obesity values in women with subclinical hypothyroidism: a double-blind randomized controlled trial - Safari, Sara; Rafraf, Maryam; Malekian, Mahsa; Molani-Gol, Roghayeh; Asghari-Jafarabadi, Mohammad; Mobasseri, Majid (Frontiers in Endocrinology, 2023)
Purpose: Subclinical hypothyroidism is an early, mild form of hypothyroidism that may progress to overt hypothyroidism if untreated. The current study aimed to assess the effects of vitamin D supplementation on hormonal (thyroid stimulating hormone [TSH], triiodothyronine, thyroxine, and free thyroxine) parameters, lipid profiles, serum irisin, and obesity indices in women with subclinical hypothyroidism. Methods: The present randomized, double-blind, placebo-controlled clinical trial was carried out on 44 women with subclinical hypothyroidism. The participants were allocated to two groups (22 patients in each group) that received vitamin D (50,000 IU/week) or placebo for 12 weeks. Fasting blood samples, anthropometric and body composition measurements, physical activity levels, and dietary intakes were collected at baseline and at the end of the study. Results: Vitamin D supplementation significantly decreased TSH, total cholesterol, and fat mass percentage, and significantly increased serum vitamin D and irisin levels and fat-free mass percentage compared to the control group (all, p<0.05). Changes in thyroid hormones, other lipid profiles, and anthropometric indices were not significantly different between the groups. Conclusion: Our study indicates that vitamin D administration improves serum TSH, total cholesterol, irisin, and body composition in women with subclinical hypothyroidism. More well-designed clinical trials are required to confirm these findings and clarify the effects of vitamin D supplementation on both genders of patients.